Cosmological scenarios from multiquintessence - Correa, R. A.C.; Moraes, P. H.R.S.; de Souza Dutra, A. [UNESP]; Santos, J. R.L.; de Paula, W. (Springer Nature, 2018)
In this work we derive and analyse cosmological scenarios coming from multi-component scalar field models. We consider a direct sum of a sine-Gordon with a Z2 model, and also a combination of those with a BNRT model. Moreover, we work with a modified version of the BNRT model, which breaks the Z2 × Z2 symmetry of the original BNRT potential, coupled with the sine-Gordon and with the standard Z2 models. We show that our approach can be straightforwardly elevated to N fields. All the computations are made analytically and some parameters restriction is put forward in order to get in touch with complete and realistic cosmological scenarios.